Evaluating the Frequency of Mole Checks by a Dermatologist and Correlated Variables in a Global Survey across 17 Countries: HELIOS Project - Henry William Lim; Thierry Passeron; Chee Leok Goh; Hee Young Kang; Fatimata Ly; Akimichi Morita; Jorge Ocampo-Candiani; Susana Puig; Sergio Schalka; Liu Wei; Anne Laure Demessant; Caroline Le Floc'h; et al. (Medical Journals Sweden, 2024)
Secondary prevention of skin cancer consists in early detection of malignant lesions through patients' mole self-examination and medical examination. The objective of this study was to assess the self-reported  frequency of mole examination in a large, representative sample of the adult general population of 17 countries from all continents. Of a total of 17,001 participants, 4.8% had their moles checked by a dermatologist more than once a year, 11.3% once a year, 8.4% every 2-3 years, 12.4% once in a while, 10.3% once in lifetime, and 52.6% of participants had never performed a mole examination. Egypt was the country with the highest prevalence of people who performed a moles check more than once a year (15.9%), followed by Brazil and the USA. A higher frequency of mole checks was associated with sex (man vs woman), higher education, higher income, fair phototype, history of skin cancer, medical insurance, and sun-protective behaviours. Despite recommendations by health providers, it appears that the frequency of mole checks in the general population is still low. It is necessary for dermatologists to keep informing at-risk populations about the importance of moles check, with particular care regarding categories that less frequently adhere to secondary prevention measures.